Trends in the number of extreme hot SST days along the Canary Upwelling System due to the influence of upwelling - Xurxo Costoya (Frontiers in Marine Science, 2014)
Trends in the number of extreme hot days (days with SST anomalies higher than the 95% percentile) were analyzed along the Canary Upwelling Ecosystem (CUE) over the period 1982- 2012 by means of SST data retrieved from NOAA OI1/4 Degree. The analysis will focus on the Atlantic Iberian sector and the Moroccan sub- region where upwelling is seasonal (spring and summer) are permanent, respectively. Trends were analyzed both near coast and at the adjacent ocean where the increase in the number of extreme hot days is higher. Changes are clear at annual scale with an increment of 9.8±0.3 (9.7±0.1) days dec-1 near coast and 11.6±0.2 (13.5±0.1) days dec-1 at the ocean in the Atlantic Iberian sector (Moroccan sub-region). The differences between near shore and ocean trends are especially patent for the months under intense upwelling conditions. During that upwelling season the highest differences in the excess of extreme hot days between coastal and ocean locations (Δn(#days dec-1)) occur at those regions where coastal upwelling increase is high. Actually, Δn and upwelling trends have shown to be significantly correlated in both areas, R=0.88 (p<0.01) at the Atlantic Iberian sector and R=0.67 (p<0.01) at the Moroccan sub-region.